Iodine(III)-Mediated Ring-Contraction Reactions Using Halogenated and Non-halogenated Solvents - Khan, Ajmir; Nishan, Umar; Badshah, Amir; Ullah, Riaz; Ali, Essam A. (Synthesis, 2024)
The transformation of a six-membered ring into the corresponding five-membered product is an important synthetic approach used in medicinal chemistry and industrial technologies. However, the yield of the product obtained through a simple one-step reaction is lower in some reported solvent systems. Here, we present the ring contraction of 1,2-dihydronaphthalene derivatives into the corresponding indanes using an environmentally friendly reagent hydroxy(tosyloxy)iodobenzene (HTIB). This transformation is achieved in both non-halogenated and halogenated solvents. We show that the halogenated solvent system not only increased the yield of the anticipated product but also reduced the formation of by-products. This study delivers an important development regarding the effectiveness of hypervalent iodine reagents in halogenated and non-halogenated solvents for ring-contraction reactions.
Keywords: six-membered rings; ring contraction; HTIB; five-membered rings; halogenated solvents